Planificación estratégica y su relación con la ejecución presupuestal en la Municipalidad Distrital de San Juan Bautista, 2023 - Arteaga Perez, Angie Stefanie (2024)
The general objective of this research work is "To determine the relationship between strategic planning and budget execution of the district municipality of San Juan Bautista, 2023." It is also recognized as a descriptive correlational, quantitative study that describes the development of events. The Pearson correlation coefficient is 0.705**, indicating a significant positive correlation between the first and second variables. In conclusion, there is a meaningful relationship between the first and second variables.